Profil content scale minnesota multiphasic personality inventory-2 (MMPI-2) adaptasi Indonesia pada komunitas â€œpunkâ€ di kawasan Megamas Manado - Mokiwang, Lavenia E.; Dundu, Anita; Kairupan, Bernabas H.R. (e-CliniC, 2016)
Abstract: "Punk" community is already scattered around the world, including Indonesia. The "punk" community is popular with their unique styles such as ripped jeans, sassy ear pin, necklace and bracelet, as well as spike-top and Mohican hair style. Music is also included in the "punk" community unique style because the music they created was a part of a rebellion, therefore, the lyrics are often without simile. The appearance and the unique styles of the "punk" community often result in negative specullation of the society towards them which can cause impact to the mental and personality of the "punk" community members. This was a cross-sectional survey study to obtain the personality and the mental status of the "punk" community members by using Content Scale MMPI-2 Indonesia Adaptation. Data were univariate analyzed using Microsoft Excel. The results showed that from 33 people who did the test, only 30 people were valid and their socio demographic data showed that the highest frequency was male (86.67%). Score distribution of content scale MMPI-2 from the highest to the lowest was as foolows: BIZ (83.33%), DEP (73.33%), FAM (73.33%), TRT (73.33%), FRS (70%), LSE (70%), HEA (63.33%), WRK (60%), ANX (56.67%), OBS (56.67%), ASP (53.33%), ANG (33.33)%, CYN (33.33%), TPA (16.67%), and SOD (3.33%).Keywords: "punk" community, profile, content scale, MMPI-2Â Abstrak: Komunitas â€œpunkâ€ saat ini sudah tersebar di dunia, termasuk Indonesia. Komunitas â€œpunkâ€ terkenal dengan gayanya yang khas yaitu celana jeans yang sobek-sobek, peniti centil di telinga, kalung dan gelang serta gaya rambut spike-top dan Mohican. Musik juga termasuk dalam gaya khas komunitas â€œpunkâ€ karena musik yang mereka ciptakan ialah bagian dari pemberontakan sehingga tak jarang lirik dari musiknya juga tidak diberi kiasan. Penampilan dan gaya khas dari komunitas â€œpunkâ€ seringkali menimbulkan pemikiran negatif dari masyarakat yang bisa berdampak pada mental dan kepribadian dari anggota komunitas â€œpunkâ€. Jenis penelitian ialah survei potong lintang untuk mengetahui kepribadian dan mental anggota komunitas â€œpunkâ€ dengan menggunakan skala content scale MMPI-2 Adaptasi Indonesia. Data dianalisis secara univariat dengan menggunakan Microsoft Excel. Hasil penelitian memperlihatkan bahwa dari 33 orang yang mengikuti tes hanya 30 orang yang dinyatakan valid dan data sosio demografi menunjukkan frekuensi jenis kelamin laki-laki yang terbanyak (86,67%). Distribusi skor tinggi Content Scale MMPI-2 berturut-turut dari yang paling tinggi ke rendah yaitu BIZ (83.33%), DEP (73.33%), FAM (73.33%), TRT (73.33%), FRS (70%), LSE (70%), HEA (63.33%), WRK (60%), ANX (56.67%), OBS (56.67%), ASP (53.33%), ANG (33.33)%, CYN (33.33%), TPA (16.67%), dan SOD (3.33%). Kata kunci: komunitas â€œpunkâ€, profil, content scale, MMPI-2